2021
DOI: 10.31635/ccschem.020.202000330
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Elastin Molecule Modulates Alzheimer’s Aβ Dynamics In Vitro and In Vivo by Affecting Microglial Activities

Abstract: suggest this revelation of the diverse functions of ELPs and other ECM may pave the way to uncover new specific microglia-targeted approaches related to AD and potentially other neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Apart from mass loss and fibrosis, several disorders, including diabetes and Alzheimer's disease, are associated with aging [55]. A recent study showed that elastin in the brain might induce pathological changes in Alzheimer's disease, and elastin is known to be fragmented and released with aging [56]. Significant ECM changes, including increased expression of collagen IV and fibronectin, are presumed to affect disease progression in patients with Alzheimer's disease [16].…”
Section: Tissue Dysfunctionsmentioning
confidence: 99%
“…Apart from mass loss and fibrosis, several disorders, including diabetes and Alzheimer's disease, are associated with aging [55]. A recent study showed that elastin in the brain might induce pathological changes in Alzheimer's disease, and elastin is known to be fragmented and released with aging [56]. Significant ECM changes, including increased expression of collagen IV and fibronectin, are presumed to affect disease progression in patients with Alzheimer's disease [16].…”
Section: Tissue Dysfunctionsmentioning
confidence: 99%
“…There are three components involved in the assembly process, including positively charged protein, [21] carboxylated PEG and chemotherapeutic ALD. The PCP is derived from elastin‐like protein with randomly coiled sequence (VPGKG) 72 and present non‐immunogenicity particularly in the context of in vivo translations (Figure S1,S2) [22–24] . Before functional assembly and in vivo experiments, we purified PCP to collect endotoxin‐free and high‐purity sample for electrostatically complexation of anionic PEG moieties (Figure S3), yielding a non‐ covalently assembled protein nanoparticulate system.…”
Section: Figurementioning
confidence: 99%
“…Currently, elastins, spider silk spidroins, collagen, and bovine serum albumin (BSA) are the most common proteins used for the fabrication of protein-based biomaterials, showing promising applications in biomedicines, tissue engineering. [14][15][16][17][18][19] However, it is still difficult to translate these unique properties of nature proteins directly into synthetic materials just by conventional synthetic methods. The tedious synthetic routes are often needed as well as their weak biocompatibility/biodegradability limited their biomedical applications.…”
Section: Introductionmentioning
confidence: 99%